Primary Cutaneous Rhabdomyosarcoma in an Adult - Cobanoglu, Bengu; Kandi, Basak; Okur, Ihsan (Wiley-Blackwell Publishing, Inc, 2009)
The authors have indicated no significant interest with commercial supporters.
Keywords: Alveolar Rhabdomyosarcoma